OP0242 Selective Deletion of Fap Expressing Cells Attenuates Synovial Inflammation and Protects against Inflammatory Bone Changes. (15th July 2016) - Croft, A.P.; Campos, J.; MacKenzie, M.; Filer, A.; Fearon, D.; Desanti, G.; Barone, F.; Buckley, C.
Abstract : Background: Despite their role as key effector cells driving synovial inflammation and joint damage, fibroblast like synoviocytes (FLS) have yet to be targeted therapeutically. Fibroblast activation protein (FAP) is a cell surface serine protease, known to be expressed at a low level in resting FLS but up-regulated during inflammation (1). Genetic deletion of FAP has been shown to protect against cartilage damage despite no protective effect on inflammation or bone erosion (2). The pathogenic role of FLS expressing FAP is currently unknown. Objectives: To determine the role of FAP expressing FLS in a murine model of autoantibody mediated inflammatory arthritis. Methods: We utilized a transgenic mouse in which FAP expressing cells were conditionally ablated (FAP-DTR) by administration of diphtheria toxin (3) in either in a prophylactic or therapeutic regime. Inflammatory polyarthritis was induced by the passive transfer of K/BxN serum into naïve mice. Mice were scored for clinical signs of arthritis and flow cytometry of digested synovial tissue was performed to determine the expression of fibroblast subsets. In addition, MicroCT was performed on hind-limbs of mice 15 days following induction of arthritis to evaluate inflammatory bone changes. Results: We found that FAP expression in the human synovium predicts disease persistence in patients with early synovitis.FAP was dynamically expressed by FLS during inflammatory arthritis and defined a population of activated fibroblasts that co-express the lining layer marker Podoplanin (gp38). Therapeutic deletion of FAP+ cells during either the induction or peak phases of inflammatory arthritis significantly attenuated synovial inflammation leading to a reduction in the clinical severity of arthritis reduced inflammatory cell infiltration and protection against inflammatory bone changes as measured by micro CT. In contrast, prophylactic deletion of FAP expressing cells led to a delayed onset of inflammatory arthritis, but did not impact on subsequent clinical severity. Conclusions: These data support a pathogenic role for FAP expressing FLS in inflammatory arthritis and provide a rationale for the selective targeting of FAP+ fibroblasts as a novel therapeutic approach. References: Bauer et al. Arthritis Res Ther 2006:8(6):R171 Wäldele et al. Arthritis Res Ther. 2015:20;17:12. Kraman et al. Science. 2010:5;330(6005):827–30. Acknowledgement: This woirk was supported by an individual Wellcome Trust Postdoctoral Clinical Research Fellowship awarded to APC. Disclosure of Interest: None declared